Periprocedural interruption of anticoagulation in patients with cancer‐associated venous thromboembolism: An analysis of thrombotic and bleeding outcomes. (29th May 2019) - Shaw, Joseph R.; Douketis, James; Le Gal, Gregoire; Carrier, Marc
Abstract: Essentials Patients with cancer‐associated VTE frequently undergo invasive procedures. Data on the perioperative interruption of anticoagulation for cancer‐associated VTE are lacking. Patients with cancer‐associated VTE experience high post‐operative VTE and major bleeding rates. This patient population may warrant close follow‐up after invasive procedures. Background: Patients with cancer are at high risk for venous thromboembolic events. Venous thromboembolism (VTE) can lead to significant morbidity among patients with cancer, and is estimated to be one of the leading causes of death among cancer patients. Patients with cancer often require invasive procedures for biopsy or therapeutic purposes. There is a lack of data on postoperative outcomes following interruption of anticoagulation in this population. Objective: To assess 30‐day postoperative thromboembolic and major bleeding complication rates following the perioperative interruption of anticoagulation in patients with cancer‐associated VTE. Methods: We conducted a retrospective self‐controlled case series study with patients with cancer‐associated VTE undergoing perioperative interruption of anticoagulation at a dedicated tertiary‐care anticoagulation clinic for invasive procedures between January 2013 and March 2018. The primary efficacy and safety outcomes were the 30‐day postoperative rates of VTE and major bleeding, respectively. The secondary outcomes included the 30‐day rates of clinically relevant non‐major bleeding (CRNMB) and overall mortality. Patients undergoing multiple perioperative anticoagulation interruptions were included. Results: One hundred and forty‐six patients undergoing 171 periprocedural interruptions were included in our cohort. The 30‐day rates of VTE and major bleeding were both 4.1% (95% confidence interval [CI] 2.0‐8.2). The 30‐day rate of CRNMB was 2.9% (95% CI 1.3‐6.7) and the 30‐day overall mortality rate was 0.6% (95% CI 0.1‐3.4). There were no fatal postoperative VTE or major bleeding events. Conclusions: The periprocedural interruption of anticoagulation in patients with cancer‐associated VTE is associated with high postoperative rates of VTE and major bleeding. Patients with cancer‐associated VTE may require closer follow‐up for VTE and bleeding complications after invasive procedures.